Is specialization desirable in committee decision making? - Ruth Ben-Yashar; Winston T. H. Koh; Shmuel Nitzan (Bar-Ilan University, Department of Economics, 2009)
Committee decision making is examined in this study focusing on the role assigned to the committee members. In particular, we are concerned about the comparison between committee performance under specialization and non-specialization of the decision makers.
Keywords: D81; D71; 330; project selection; public policy; collective decision making; committee; uncertain dichotomous choice; specialization; simple majority rule; Politische Entscheidung; Gruppenentscheidung; Entscheidung bei Unsicherheit; Abstimmungsregel; Neue politische Ökonomie